Epigenetic regulation in diabetic vascular complications. (November 2019) - Jin, Jiayu; Wang, Xinhong; Zhi, Xiuling; Meng, Dan
Abstract : Cardiovascular disease (CVD), the main complication of diabetes mellitus (DM), accounts for a high percentage of mortality in diabetic patients. Endothelial dysfunction is a major causative event in the pathogenesis of diabetes-related vascular disease and the earliest symptom of vascular injury. Epigenetic modification plays a key role in the initiation, maintenance, and progression of both endothelial dysfunction and diabetes. Epigenetic alterations respond to the environment and mediate the 'legacy effect' of uncontrolled hyperglycaemia early in the disease despite thorough glycaemic control in a phenomenon called metabolic memory. Therefore, an understanding of the integrated system of different epigenetic mechanisms in DM and its vascular complications is urgently needed. This review summarizes aberrant epigenetic regulation under diabetic conditions, including histone modifications, DNA methylation, and non-coding RNAs (ncRNAs). Understanding the connections between these processes and DM may reveal a novel potential therapeutic target for diabetic vascular complications.